The anatomy and phylogenetic position of the erythrosuchid archosauriform Guchengosuchus shiguaiensis from the earliest Middle Triassic of China - Butler, Richard J. (2019)
Erythrosuchidae is a clade of early archosauriform reptiles, which were apex predators in many late Early and Middle Triassic ecosystems, following the Permo-Triassic mass extinction. Erythrosuchids had a worldwide distribution, with well-preserved fossil material known from South Africa, European Russia, and China. We here redescribe the anatomy and revise the taxonomy of Guchengosuchus shiguaiensis, which is one of the stratigraphically oldest erythrosuchids and is known from a single partial skeleton from the lowermost Middle Triassic (lower Anisian) lower Ermaying Formation of Shaanxi Province, China. We provide a new differential diagnosis for Guchengosuchus shiguaiensis, and identify a series of autapomorphies relating to the morphologies of the skull roof and vertebrae. Incorporating updated anatomical information for Guchengosuchus into the most comprehensive morphological phylogenetic analysis available for early archosauromorphs recovers it as an early branching member of Erythrosuchidae, outside of the clade formed by Garjainia, Erythrosuchus, Chalishevia, and Shansisuchus. Fugusuchus hejiapanensis, from the uppermost Lower Triassic to lower Middle Triassic Heshanggou Formation of China, is recovered as the earliest branching member of Erythrosuchidae.